How sexual and natural selection shape sexual size dimorphism: Evidence from multiple evolutionary scales. (3rd May 2019) - Littleford‐Colquhoun, Bethan L.; Clemente, Christofer; Thompson, Graham; Cristescu, Romane H.; Peterson, Nicola; Strickland, Kasha; Stuart‐Fox, Devi; Frere, Celine H.
Abstract: Sexual size dimorphism (SSD) is pervasive across taxa and reflects differences in the effects of sexual and natural selection on body size between the sexes. However, disentangling the complex eco‐evolutionary interactions between these two mechanisms remains a major challenge for biologists. Here, we combine macro‐evolutionary (between‐species), local evolutionary (between‐population) and fine‐scale evolutionary (within‐population) patterns of SSD to explore how sexual and natural selection interact and shape the evolution of SSD in Australian agamid lizards. Australian agamid lizards show substantial variation in SSD, ecological traits and species density making them an ideal study system to address this question. At the between‐species level, population density, ecological generalism and mean species size significantly predict SSD variation; however, only ecological generalism was found to significantly explain variation in larger‐than‐average male‐biased SSD. At the population level, density positively correlated with SSD in native habitats, but not city park habitats. Last, agonistic behaviour acted as the primary driver of SSD at the within‐population level. Our results indicate how sexual and natural selection can interact at different evolutionary scales, and show the importance of considering both selective mechanisms when investigating patterns of SSD. Aplain language summary is available for this article. Abstract : Plain Language Summary